Q: What is the answer to 6v s 5s - 4v 2s 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is only because we count in tens - and 5 10 and 2 are factors.

(1/2s)+(1/5x)+7 5s+2x+7 5s=2x+7 s=2/5x+7/5 (1/2(2/5x+7/5))+(1/5x)+7 1/5x+3.5/5+1/5x+7 2/5x+7 7/10 2/5x=-7 7/10 x=-19.25 (1/2s)+(1/5x)+7 1/2s-3.85+7 1/2s+3.15 1/2s=-3.15 s=-6.3 (1/2s)+(1/5x)+7 1/2(-6.3)+1/5(-19.25)+7 -3.15-3.85+7 0 In the end, it equals 0 because there were no values for x and s and since I started with just an equation with nothing on the other side, I used (by default) 0 on the other side.

If 2s = 5 then s = 2.5. So by letting s equal 2.5 (two and one half) you will allow 2s to equal 5.

-v + 5 + 6v = 1 + 5v + 3Clean up and combine each side:(-v + 6v) + 5 = (1 + 3) + 5v5v + 5 = 4 + 5vSubtract 5v from each side:5 = 4.There is no solution.No value of 'v' can make [ 5 = 4 ].

-20v + 4v2 - 5y + vy = 4v2 - 20v + vy - 5y = 4v*(v - 5) + y*(v - 5) = (4v + y)*(v - 5)

Related questions

if s is 2, 2s is 4. 3 squared is 9. 4 + 9 = 13. 13 / 5 = 2.6, which is not equal to 2.

It is only because we count in tens - and 5 10 and 2 are factors.

That's a simple example of system of equations. There are quite a number of methods for solving those, but the easiest here would be to calculate one variable from first equation and substitute it into second. 2s + 3t = 28 5s + 6t = 61 Let's calculate s from the first equation: 2s + 3t = 28, 2s = 28 - 3t s = 14 - 3t/2 Substitute s into second equation 5s + 6t = 61, 5(14 - 3t/2) + 6t = 61, 70 - 15t/2 + 6t = 61, 70 - 3t/2 = 61, 3t/2 = 9, t = 6. We can then substitute t back into first equation: 2s + 3t = 28, 2s + 3 * 6 = 28, 2s = 10, s = 5. So the final answer is: s = 5 t = 6

5(6v + 7)(6v - 7)

5 5s equals 25.

5s

If p = 2s + 5, then s = (p-5)/2 or 1/2 (p-5) --- p = 2s +5 p-5 = 2s (p-5)/2 = s

(1/2s)+(1/5x)+7 5s+2x+7 5s=2x+7 s=2/5x+7/5 (1/2(2/5x+7/5))+(1/5x)+7 1/5x+3.5/5+1/5x+7 2/5x+7 7/10 2/5x=-7 7/10 x=-19.25 (1/2s)+(1/5x)+7 1/2s-3.85+7 1/2s+3.15 1/2s=-3.15 s=-6.3 (1/2s)+(1/5x)+7 1/2(-6.3)+1/5(-19.25)+7 -3.15-3.85+7 0 In the end, it equals 0 because there were no values for x and s and since I started with just an equation with nothing on the other side, I used (by default) 0 on the other side.

Is it 4v-7+8v+4-5 ? If so then you're answer is 12v-8

5/5=1 Keep this for later. so 2 5s used. Then do 5*5=25, so 5 5s used as 25 has a five in it, now do 1 - 25=24.

22 5s - 3 = 5(5) - 3 = 25-3 = 22

It is correct to say iPhone 5S is an upgraded iPhone 5.